Creation, implementation and management of innovation on the example of Openbravo S.L. - Karwala Filip (My University, 2007)
The main goal of this thesis was to analyze the process of innovation in Openbravo. Firstly, to look on what is innovative and where innovation in Openbravo comes from. Secondly, how innovation is created and implemented into the company, and its outcomes. Next, it was aimed to analyze the procedure of innovation management in Openbravo – its way of recognizing potential of innovation, its strategy and organizational structure, and its system of innovation control. The hypothesis was that the incremental innovation in technology based startup companies is the main factor of value creation. The paper consists of two parts – theoretical and empirical. The first two chapters are theoretical, and the third one is empirical. The first chapter consists of four subchapters. The first one defines the concept and describes the types of innovation. The second explains where innovation comes from – the sources of innovation. The third subchapter analyzes the factors that influence the effectiveness of making an innovative opportunity a real innovation – transfer of innovation. The last part of the first chapter presents different models that explain the innovation’s impact on firm’s and market capabilities depending of the innovation’s type. The second chapter is focused on the process of innovation management, and is divided into four subchapters. The first one describes how companies recognize the potential of innovation and what the factors that influence this process are. The second subchapter is focused on strategic choice of innovation strategy. The third subchapter explains how companies design and organize their innovation portfolios. Finally, the last part of the second chapter analyzes the innovation system and the process of bringing innovation into market. The third chapter – the empirical one, is an analysis of the processes of innovation in Openbravo. First, the goals and methodology of the analysis are described. In the second part, the business model of Openbravo and its competitive environment is described. The third subchapter explains all the characteristics of Openbravo’s product and services. The chapter ends with a broad analysis of Openbravo’s innovation management process. The chapter ends with conclusion about the analysis, and with suggestions based on personal experience. The theoretical part of the paper is based on management and economic literature – books, articles, and internet resources. The empirical part is based on personal experience in Openbravo during the period of over six months, personal interviews with the members of the executive team and on conversations with other employees.
Tworzenie, wdrażanie i zarządzanie innowacją na przykładzie Openbravo S.L.
Keywords: innovation; management of innovaton; Openbravo S.L.